2018
DOI: 10.1016/j.apt.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Joule heating and buoyancy effects in electro-osmotic peristaltic transport of aqueous nanofluids through a microchannel with complex wave propagation

Abstract: Ti t l e Joul e h e a ti n g a n d b u oy a n cy eff e c t s in el e c t r o-o s m o tic p e ri s t al tic t r a n s p o r t of a q u e o u s n a n ofl ui d s t h r o u g h a m i c r o c h a n n el wi t h c o m pl ex w a v e p r o p a g a tio n A u t h o r s B e g, OA, Tri p a t hi, D a n d S h a r m a , A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 44 publications
(40 reference statements)
0
40
0
Order By: Relevance
“…For an incompressible viscous electromagnetic nanofluid, the balance equations for mass, momentum, energy (heat), and nanoparticle volumetric fraction (concentration) are given by: trueU¯trueX¯goodbreakinfix+trueV¯trueY¯goodbreakinfix=0, ρf[trueU¯t+trueU¯trueU¯trueX¯+trueV¯trueU¯trueY¯]goodbreakinfix=trueP¯trueX¯goodbreakinfix+μ[2trueU¯X¯2+2trueU¯Y¯2]goodbreakinfix−σB02trueU¯goodbreakinfix+ρ¯eEx, ρf[trueV¯t+trueU¯trueV¯trueX¯+trueV¯trueV¯trueY¯]goodbreakinfix=trueP¯trueY¯goodbreakinfix+μ[2trueV¯X¯2+2trueV¯Y¯2]<...>…”
Section: Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…For an incompressible viscous electromagnetic nanofluid, the balance equations for mass, momentum, energy (heat), and nanoparticle volumetric fraction (concentration) are given by: trueU¯trueX¯goodbreakinfix+trueV¯trueY¯goodbreakinfix=0, ρf[trueU¯t+trueU¯trueU¯trueX¯+trueV¯trueU¯trueY¯]goodbreakinfix=trueP¯trueX¯goodbreakinfix+μ[2trueU¯X¯2+2trueU¯Y¯2]goodbreakinfix−σB02trueU¯goodbreakinfix+ρ¯eEx, ρf[trueV¯t+trueU¯trueV¯trueX¯+trueV¯trueV¯trueY¯]goodbreakinfix=trueP¯trueY¯goodbreakinfix+μ[2trueV¯X¯2+2trueV¯Y¯2]<...>…”
Section: Mathematical Modelmentioning
confidence: 99%
“…For an incompressible viscous electromagnetic nanofluid, the balance equations for mass, momentum, energy (heat), and nanoparticle volumetric fraction (concentration) are given by: [51][52][53][54]…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in buoyancy-driven flows, although the difference in inertia is almost negligible, the gravity remains sufficiently strong to make the specific weight significantly different during the flow in multiphase fluids. Tripathi et al [14] investigated buoyancy effects in the peristaltic flow of nanofluid under the influence of electro-osmosis. Animasaun and Pop [15] numerically explored the effects of buoyancy on the flow driven by catalytic surface reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Tripathi et al [ 29 ] worked on the combined effect of electroosmosis and peristalsis through the microchannel. In addition, Tripathi et al [ 30 ] revealed the peristaltic transport of nanofluids with buoyancy effect via a microchannel. The impact of heat and mass transport for the combined effect of electroosmosis and peristalsis was studied by Waheed et al [ 31 ].…”
Section: Introductionmentioning
confidence: 99%